Sodium-rich O3 phase positive electrode material, preparation method thereof and sodium ion battery

By preparing Na1.2Li0.1Ru0.6Mn0.1O2 sodium-rich O3 phase positive electrode material, spray pyrolysis and sintering processes are used to solve the difficulty of activate anion redox properties in O3 phase layered oxides, and the structural stability of sodium ion batteries is achieved Improved properties and electrochemical properties.

CN119153677APending Publication Date: 2024-12-17ZHUJI PAWA NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411543006.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

It is difficult to activate the anionic redox properties of sodium ion batteries in O3-phase layered oxides, and it is difficult to prepare a sodium-rich cathode material with a single O3-phase structure, resulting in poor structural stability and capacity attenuation.

Method used

Na1.2Li0.1Ru0.6Mn0.1O2 is used as the sodium-rich O3-phase positive electrode material, and is prepared by spray pyrolysis and sintering processes to reasonably regulate the content of Ru and Mn, ensure the formation of pure O3 phase, and be replaced by Na-O-Li. Reduce lattice mismatch, improve structural stability and electrochemical properties.

Benefits of technology

The good structural stability and electrochemical performance of sodium-rich O3-phase positive electrode material are achieved, the cycle performance and capacity retention of the battery are improved, and the stability at high voltage is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153677A_ABST
    Figure CN119153677A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-rich O3 phase positive electrode material, a preparation method thereof and a sodium ion battery. The chemical formula of the sodium-rich O3 phase positive electrode material is Na1. 2Li0. 1Ru0. 6Mn0. 1O2. The positive electrode material has good structural stability and electrochemical performance; the sodium-rich O3 phase positive electrode material Na1. 2Li0. 1Ru0. 6Mn0. 1O2 with good structural stability and electrochemical performance is obtained through spray pyrolysis and sintering by adopting proper raw materials and a raw material ratio, and the sodium-rich O3 phase positive electrode material Na1. 2Li0. 1Ru0. 6Mn0. 1O2 shows good cycling stability and capacity when being applied to a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular relates to a sodium-rich O3 phase positive electrode material and a preparation method and application thereof. Background Art

[0002] In the positive electrode materials of layered sodium ion batteries, the electrochemical activity of oxygen in the system can be stimulated by introducing additional sodium ions, providing additional capacity for the materials. However, due to the large ionic radius of sodium ions, the NaO6 and TMO6 octahedrons show a large lattice mismatch in configuration, which makes the layered positive electrode materials of sodium ion batteries have more configurations than lithium ion batteries, further resulting in the diversification of the ways to activate the electrochemical activity of layered oxygen elements; in the P2 phase layered oxide, by introducing vacancies through doping with non-electrochemically active elements, the Na-OA (A is a non-electrochemically active element) configuration is formed locally, which can stimulate the anionic redox activity of the system in the P2 phase layered oxide; while it is relatively difficult to activate the anionic redox characteristics of the system in the O3 phase layered oxide, mainly because it is difficult to prepare sodium-rich positive electrode materials with a single O3 phase structure after increasing the Na-O-Na content, and most of them are complex mixed phases.

[0003] 2Ru 1-x Mn x In O3 (0≤x≤1), when x>0.3, the system presents a variety of diffraction patterns and is no longer a single O3 phase structure. The complex composite phase has a huge capacity decay during the charge and discharge process and has poor structural stability, making it impossible to further develop and utilize it. Summary of the invention

[0004] In response to the above technical problems, the present application provides a novel sodium-rich O3 phase positive electrode material and a preparation method thereof, and a sodium ion battery.

[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a sodium-rich O3 phase positive electrode material is provided, wherein the chemical formula of the sodium-rich O3 phase positive electrode material is Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

[0006] Furthermore, the sodium-rich O3 phase positive electrode material is a single crystal morphology; the particle size of the sodium-rich O3 phase positive electrode material is 1~3μm.

[0007] In a second aspect, a method for preparing a sodium-rich O3 phase positive electrode material precursor is provided, comprising: A ruthenium source and a manganese source are prepared into a mixed solution A; a sodium source and a lithium source are prepared into a mixed solution B; Using the mixed solution A and the mixed solution B as raw materials, spray pyrolysis is performed to obtain a powder material; The powder material is sintered to obtain a sodium-rich O3 phase positive electrode material Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

[0008] Furthermore, the sintering is firstly heated to 700-800°C and kept warm for 4-6 hours, and then heated to 900-950°C and kept warm for 8-10 hours; the sintering atmosphere is air atmosphere.

[0009] Furthermore, during spray pyrolysis, the feed of the mixed solution A and the mixed solution B is set according to a molar ratio of Na, Li, Ru and Mn contained in the feed per unit time of 1.2~1.32:0.1~0.11:0.6:0.1.

[0010] Furthermore, during the spray pyrolysis, the mixed liquid A and the mixed liquid B are sprayed into the spray pyrolysis device by a carrier gas.

[0011] Furthermore, the carrier gas includes any one of compressed air, compressed nitrogen or compressed argon, or a combination of at least two of them; preferably, the flow rate of the carrier gas is 2-6 L / min.

[0012] Furthermore, the temperature of the spray pyrolysis is 600-800°C.

[0013] Furthermore, the molar ratio of Ru in the ruthenium source to Mn in the manganese source in the mixed solution A is 6:1.

[0014] Furthermore, the total metal ion concentration in the mixed solution A is 3-5 mol / L.

[0015] Furthermore, in the mixed solution B, the molar ratio of Na contained in the sodium source to Li contained in the lithium source is 1.2~1.32:0.1~0.11.

[0016] Furthermore, the total metal ion concentration in the mixed solution B is 3-5 mol / L.

[0017] Furthermore, the ruthenium source is one or more of ruthenium nitrate and its hydrate, ruthenium acetate and its hydrate.

[0018] Furthermore, the manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, and manganese oxalate and its hydrate.

[0019] Furthermore, the sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium oxalate.

[0020] Furthermore, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium acetate, and lithium oxalate.

[0021] In a third aspect, a sodium ion battery is provided, comprising the aforementioned sodium-rich O3 phase positive electrode material or the sodium-rich O3 phase positive electrode material prepared by the aforementioned preparation method.

[0022] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: A new type of sodium-rich O3 phase positive electrode material is provided, whose chemical formula is Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2, the positive electrode material has good structural stability and electrochemical performance.

[0023] A novel method for preparing a sodium-rich O3 phase positive electrode material is provided, wherein a sodium-rich O3 phase positive electrode material Na with good structural stability and electrochemical performance is obtained by using appropriate raw materials and raw material ratios, through spray pyrolysis and sintering. 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The XRD diagrams of the positive electrode materials prepared in Example 1 and Comparative Examples 1-3.

[0026] Figure 2 It is a partial enlarged view of the XRD pattern of the positive electrode materials prepared in Example 1 and Comparative Examples 1 to 3.

[0027] Figure 3 This is the SEM image of the positive electrode material prepared in Example 1.

[0028] Figure 4 Cycling curves of button cells assembled with the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION

[0029] The present invention provides a sodium-rich O3 phase positive electrode material, wherein the chemical formula of the sodium-rich O3 phase positive electrode material is Na 1.2 Li 0.1 Ru0.6 Mn 0.1 O2.

[0030] Na-O-Li is used to replace part of Na-O-Na, while further increasing the content of Na-OA (A is an alkali metal) in the system, reducing the content of Na in the transition metal layer and reducing the lattice mismatch; Ru doping is beneficial to provide the system with a stronger Ru-O bond, thereby stabilizing the anion redox characteristics of the system, and by reasonably regulating the content of Ru and Mn, ensuring the formation of a pure O3 phase, the sodium-rich O3 phase positive electrode material has good electrochemical properties.

[0031] In some preferred embodiments, the sodium-rich O3 phase positive electrode material is a single crystal morphology, which is more difficult to crack than a spherical or quasi-spherical morphology and thus has better structural stability, especially under high voltage; the particle size of the sodium-rich O3 phase positive electrode material is 1~3μm.

[0032] The present invention also provides a method for preparing a sodium-rich O3 phase positive electrode material precursor, comprising: A ruthenium source and a manganese source are prepared into a mixed solution A; a sodium source and a lithium source are prepared into a mixed solution B; Using the mixed solution A and the mixed solution B as raw materials, spray pyrolysis is performed to obtain a powder material; The powder material is sintered to obtain a sodium-rich O3 phase positive electrode material Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

[0033] In some preferred embodiments, the sintering is firstly heated to 700-800° C. and kept at this temperature for 4-6 hours, and then heated to 900-950° C. and kept at this temperature for 8-10 hours; the sintering atmosphere is an air atmosphere.

[0034] In some preferred embodiments, during spray pyrolysis, the feed of the mixed solution A and the mixed solution B is set according to a molar ratio of Na, Li, Ru and Mn contained in the feed per unit time of 1.2~1.32:0.1~0.11:0.6:0.1.

[0035] In some preferred embodiments, during the spray pyrolysis, the mixed liquid A and the mixed liquid B are sprayed into the spray pyrolysis device by a carrier gas. In some preferred embodiments, the carrier gas includes any one of compressed air, compressed nitrogen or compressed argon, or a combination of at least two of them.

[0036] In some preferred embodiments, the flow rate of the carrier gas is 2-6 L / min.

[0037] In some preferred embodiments, the spray pyrolysis temperature is 600-800°C.

[0038] In some preferred embodiments, the molar ratio of Ru in the ruthenium source to Mn in the manganese source in the mixed solution A is 6:1.

[0039] In some preferred embodiments, the total metal ion concentration in the mixed solution A is 3-5 mol / L.

[0040] In some preferred embodiments, in the mixed solution B, the molar ratio of Na contained in the sodium source to Li contained in the lithium source is 1.2-1.32:0.1-0.11.

[0041] In some preferred embodiments, the total metal ion concentration in the mixed solution B is 3-5 mol / L.

[0042] In some preferred embodiments, the ruthenium source is one or more of ruthenium nitrate and its hydrate, ruthenium acetate and its hydrate.

[0043] In some preferred embodiments, the manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, and manganese oxalate and its hydrate.

[0044] In some preferred embodiments, the sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium oxalate.

[0045] In some preferred embodiments, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium acetate, and lithium oxalate.

[0046] The present invention also provides a sodium ion battery, comprising the aforementioned sodium-rich O3 phase positive electrode material or the sodium-rich O3 phase positive electrode material prepared by the aforementioned preparation method.

[0047] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0048] Example 1 Step 1: preparing a mixed solution A with ruthenium nitrate and manganese nitrate, wherein the molar ratio of ruthenium nitrate to manganese nitrate in the mixed solution A is 6:1, and the total metal ion concentration in the mixed solution A is 3 mol / L; preparing a mixed solution B with sodium carbonate and lithium carbonate, wherein the total molar concentration of sodium and lithium in the mixed solution B is 3 mol / L; and the molar ratio of Ru, Mn, Na and Li in the mixed solution A to the mixed solution B is 1.32:0.11:0.6:0.1; Step 2: start the spray pyrolysis furnace, the mixed liquid A and the mixed liquid B are sprayed into the spray pyrolysis furnace by compressed air (specifically, the mixed liquid A and the mixed liquid B are first atomized, and then the atomized droplets are sent into the spray pyrolysis furnace by a carrier gas for pyrolysis reaction), heated to 600°C, the compressed air carrier gas flow rate is 2L / min, and all metal salt solutions are added simultaneously for spray pyrolysis reaction (that is, the feed rate of the mixed liquid A and the mixed liquid B is the same), to obtain a spray pyrolysis powder material.

[0049] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere, first heat it to 700°C, calcine it for 4 hours, then continue to heat it to 900°C and calcine it for 8 hours, and cool it to room temperature with the furnace to obtain the positive electrode material.

[0050] The XRD pattern of the obtained positive electrode material is shown in Figure 1 As shown, from Figure 1 It can be seen that the positive electrode material prepared in Example 1 is a pure O3 phase sodium ion battery positive electrode material. Combined with the ratio of each element in the raw material, it can be determined that the obtained pure O3 phase sodium ion battery positive electrode material is Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2. The SEM image of the obtained positive electrode material is shown in Figure 2 As shown, from Figure 2 It can be seen that the morphology of the obtained positive electrode material is a single crystal morphology.

[0051] Example 2 Step 1: prepare a mixed metal salt solution A with ruthenium nitrate and manganese nitrate, wherein the molar ratio of ruthenium nitrate to manganese nitrate in the mixed metal salt solution A is 6:1, and the total metal ion concentration in the mixed metal salt solution A is 4 mol / L; prepare a mixed solution B with sodium acetate and lithium acetate, wherein the total molar concentration of sodium and lithium in the mixed solution B is 4 mol / L; and the molar ratio of Ru, Mn, Na and Li in the mixed metal salt solution A to the mixed metal salt solution B is 1.32:0.11:0.6:0.1; Step 2: Start the spray pyrolysis furnace, spray the mixed solution A and the mixed solution B into the spray pyrolysis furnace by compressed air, heat to 700°C, the compressed air carrier gas flow rate is 4L / min, and all metal salt solutions are added simultaneously to perform spray pyrolysis reaction to obtain a spray pyrolysis powder material.

[0052] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere, first heat it to 800 ° C, calcine it for 5 hours, then continue to heat it to 900 ° C and calcine it for 9 hours, cool it to room temperature with the furnace, and finally obtain Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

[0053] Example 3 Step 1: prepare a mixed metal salt solution A with ruthenium nitrate and manganese nitrate, wherein the molar ratio of ruthenium nitrate to manganese nitrate in the mixed metal salt solution A is 6:1, and the total metal ion concentration in the mixed metal salt solution A is 5 mol / L; prepare a mixed solution B with sodium oxalate and lithium oxalate, wherein the total molar concentration of sodium and lithium in the mixed solution B is 5 mol / L; and the molar ratio of Ru, Mn, Na and Li in the mixed metal salt solution A to the mixed metal salt solution B is 1.32:0.11:0.6:0.1; Step 2: Start the spray pyrolysis furnace, spray the mixed solution A and the mixed solution B into the spray pyrolysis furnace by compressed air, heat to 800°C, the compressed air carrier gas flow rate is 6L / min, and all metal salt solutions are added simultaneously to perform spray pyrolysis reaction to obtain a spray pyrolysis powder material.

[0054] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere, first heat it to 800 ° C, calcine for 6 hours, then continue to heat it to 950 ° C and calcine for 10 hours, cool it to room temperature with the furnace, and finally obtain Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

[0055] Comparative Example 1 Step 1: preparing a mixed metal salt solution A with ruthenium nitrate and manganese nitrate, wherein the molar ratio of ruthenium nitrate to manganese nitrate in the mixed metal salt solution A is 2:1, and the total metal ion concentration in the mixed metal salt solution A is 3 mol / L; preparing solution B with sodium carbonate, wherein the molar concentration of sodium in the solution B is 3 mol / L; and the molar ratio of Ru, Mn and Na in the mixed metal salt solution A to that in the solution B is 1.21:0.6:0.3; Step 2: start the spray pyrolysis furnace, spray the mixed solution A and the mixed solution B into the spray pyrolysis furnace by compressed air, heat to 600°C, the compressed air carrier gas flow rate is 2L / min, and all metal salt solutions are added simultaneously to perform spray pyrolysis reaction to obtain a spray pyrolysis powder material.

[0056] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere, first heat it to 700 ° C, calcine it for 4 h, then continue to heat it to 900 ° C and calcine it for 8 h, cool it to room temperature with the furnace, and finally obtain the positive electrode material Na 1.1 Ru 0.6 Mn 0.3 O2, its XRD pattern is as follows Figure 1 As shown, from Figure 1 It can be seen that the sample prepared in Comparative Example 1 is a mixed phase O3 phase and P2 phase material. By comparing Example 1 with Comparative Example 1, it can be found that a sodium-rich O3 pure phase material can only be prepared according to an element ratio designed in a specific ratio.

[0057] The positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 were assembled into batteries in the following manner: The active materials prepared in Examples 1 to 3 and Comparative Example 1 were weighed and ground with conductive carbon and binder at a mass ratio of 8: 1: 1, transferred to a 10 mL weighing bottle, NMP solvent was dropped, and then a stirrer was added and stirred for 2 hours. A uniform film was applied on the aluminum foil, and immediately transferred to an 80°C vacuum drying oven for drying for 24 hours, and finally the pole piece was punched into a disc electrode with a diameter of 15 mm. In the glove box, button cells were assembled in the order of positive electrode shell-positive electrode sheet-diaphragm-sodium sheet-gasket-shrapnel-back shell, and the formula of the electrolyte was 1.0M NaPF6in PC: EMC (1: 1 Vol % with 4.0 %FEC). The obtained battery was tested for electrical performance: the voltage range was 2.0~4V, the current density was 1C, and the cycle was 50 times.

[0058] The results are as follows Figure 3 As shown, after the sodium-rich O3 phase positive electrode materials prepared in Examples 1 to 3 were assembled into batteries, the first cycle discharge capacities were 128.5 mAh / g, 125.4 mAh / g and 121.5 mAh / g, respectively, and the capacity retention rates after 50 cycles were 92.61%, 89.55% and 89.13%, respectively, indicating that the pure O3 phase positive electrode material has good electrical properties and cycle performance, so it also has good structural stability. After analysis, this may be due to the use of Na-O-Li to replace part of Na-O-Na, while further increasing the content of Na-OA (A is an alkali metal) in the system, while reducing the content of Na in the transition metal layer and reducing the lattice mismatch; and the doping of Ru is beneficial to provide a stronger Ru-O bond for the system, thereby stabilizing the anionic redox characteristics of the system, and by reasonably regulating the content of Ru and Mn, ensuring the formation of a pure O3 phase, the sodium-rich O3 phase positive electrode material has good electrochemical properties.

[0059] from Figure 3 By comparing the electrochemical properties of button cells assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1, it is found that the discharge specific capacity and cycle performance of the pure phase material prepared in Example 1 are significantly improved. After analysis, on the one hand, this is because the pure phase material prepared in Example 1 is a sodium-rich material, and the total amount of lithium and sodium that can be deintercalated therein is increased compared with Comparative Example 1, resulting in an improvement in the discharge specific capacity. On the other hand, it may be because the positive electrode material prepared in Comparative Example 1 is a non-O3 pure phase material, and the complex composite phase has a huge capacity decay during the charge and discharge process, and the structural stability is poor.

[0060] Comparative Example 2 The difference between this comparative example and Example 1 lies in that the sintering mechanism of step three is different. Step three is specifically as follows: sintering the spray pyrolysis powder material in an air atmosphere, first heating to 700°C, calcining for 4 hours, then continuing to heat to 1000°C and calcining for 8 hours, and cooling to room temperature with the furnace to obtain the positive electrode material.

[0061] The XRD pattern of the obtained positive electrode material is shown in Figure 1 and 2 As shown, from Figure 1 and Figure 2 It can be seen that the positive electrode material prepared in Comparative Example 1 is a mixed phase.

[0062] Comparative Example 3 The difference between this comparative example and Example 1 is that the sintering mechanism of step three is different. Step three is specifically as follows: sintering the spray pyrolysis powder material in an air atmosphere, first heating to 700°C, calcining for 4 hours, then continuing to heat to 850°C and calcining for 8 hours, and cooling to room temperature with the furnace to obtain the positive electrode material.

[0063] The XRD pattern of the obtained positive electrode material is shown in Figure 1 and 2 As shown, from Figure 1 and Figure 2 It can be seen that the positive electrode material prepared in Comparative Example 1 is a mixed phase. By comparing Example 1 with Comparative Examples 2 and 3, it can be found that a sodium-rich O3 pure phase material can only be prepared within a specific temperature range.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sodium-rich O3 phase positive electrode material, characterized in that: The chemical formula of the sodium-rich O3 phase positive electrode material is Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

2. The sodium-rich O3 phase positive electrode material according to claim 1, characterized in that The sodium-rich O3 phase positive electrode material is in a single crystal morphology; the particle size of the sodium-rich O3 phase positive electrode material is 1-3 μm.

3. A method for preparing a sodium-rich O3 phase positive electrode material, characterized in that: include: Prepare a mixed solution A with a ruthenium source and a manganese source; Prepare a mixed solution B with a sodium source and a lithium source; Using the mixed solution A and the mixed solution B as raw materials, spray pyrolysis is performed to obtain a powder material; The powder material is sintered to obtain a sodium-rich O3 phase positive electrode material Na 1.2 Li 0.1 Ru 0.6 Mn 0.1 O2.

4. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: The sintering is firstly heated to 700-800°C and kept for 4-6 hours, and then heated to 900-950°C and kept for 8-10 hours; the sintering atmosphere is air atmosphere.

5. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: During spray pyrolysis, the feed of the mixed solution A and the mixed solution B is set according to the molar ratio of Na, Li, Ru and Mn contained in the feed per unit time of 1.2~1.32:0.1~0.11:0.6:0.

1.

6. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: During the spray pyrolysis, the mixed liquid A and the mixed liquid B are sprayed into the spray pyrolysis device by a carrier gas; Preferably, the carrier gas includes any one of compressed air, compressed nitrogen or compressed argon, or a combination of at least two of them; Preferably, the flow rate of the carrier gas is 2-6 L / min.

7. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: The temperature of the spray pyrolysis is 600-800°C.

8. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: The molar ratio of Ru in the ruthenium source to Mn in the manganese source in the mixed solution A is 6:1; The total metal ion concentration in the mixed solution A is 3-5 mol / L; In the mixed solution B, the molar ratio of Na contained in the sodium source to Li contained in the lithium source is 1.2-1.32:0.1-0.11; The total metal ion concentration in the mixed solution B is 3-5 mol / L.

9. The method for preparing a sodium-rich O3 phase positive electrode material according to claim 3, characterized in that: The ruthenium source is one or more of ruthenium nitrate and its hydrate, ruthenium acetate and its hydrate; The manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, and manganese oxalate and its hydrate; The sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate and sodium oxalate; The lithium source is one or more of lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate.

10. A sodium ion battery, characterized in that It includes the sodium-rich O3 phase positive electrode material as described in claim 1 or 2 or the sodium-rich O3 phase positive electrode material prepared by the preparation method as described in any one of claims 3 to 9.

Citation Information

Cited By

  • A sodium-rich positive electrode material and a sodium-ion battery

    CN122696668A